2023
DOI: 10.1093/jxb/erad181
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome-interacting factor PIF3 integrates phytochrome B and UV-B signaling pathways to regulate gibberellin- and auxin-dependent growth in cucumber hypocotyls

Abstract: In Arabidopsis, the photoreceptors phytochrome B- (PhyB) and UVB resistance 8- (UVR8) mediated light responses play a major role in regulating photomorphogenic hypocotyl growth, but how they crosstalk to coordinate this process is not well understood. Here we report map-based cloning and functional characterization of a UVB-insensitive, long-hypocotyl mutant, lh1, and a wild-type-like lh2 mutant in cucumber, Cucumis sativus, which encodes a defective CsPhyB and a key gibberellic acid (GA) biosynthesis enzyme C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Phytochrome-interacting factors have been discovered as regulatory hubs that integrate environmental cues into transcriptional scenarios, and functional characterizations have shown that PIF proteins are widely involved in plant growth, development, and stress response biological processes [30,31]. Several PIF genes have been identified in many species; for example, eight candidate PIF genes have been reported in Arabidopsis [9], tomatoes [12], maize [11,32], apples [13,33], and Brachypodium distachyon [15]; six have been reported in rice [10] and Physcomitrella patens [17]; and only one has been reported in Marchantia polymorpha [16].…”
Section: Stpif Identification and Evolution In Potatoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochrome-interacting factors have been discovered as regulatory hubs that integrate environmental cues into transcriptional scenarios, and functional characterizations have shown that PIF proteins are widely involved in plant growth, development, and stress response biological processes [30,31]. Several PIF genes have been identified in many species; for example, eight candidate PIF genes have been reported in Arabidopsis [9], tomatoes [12], maize [11,32], apples [13,33], and Brachypodium distachyon [15]; six have been reported in rice [10] and Physcomitrella patens [17]; and only one has been reported in Marchantia polymorpha [16].…”
Section: Stpif Identification and Evolution In Potatoesmentioning
confidence: 99%
“…Specifically, the interaction between CsPhyB and CsPIF3, followed by downstream engagement with CsGA20ox-2-DELLA and CsPIF3-CsARF18, modulates hypocotyl elongation via gibberellin and auxin routes. CsPIF3's transcriptional control is affected through its binding to G/E-box motifs within the CsGA20ox-2 and CsARF18 promoter regions [30]. Considering the central role of PIFs in light signal transduction, this study explored the effect of light intensity on StPIF expression levels.…”
Section: Pifs Function As Key Nodes Conjoining Environmental and Horm...mentioning
confidence: 99%
“…Current evidence suggests that PHYs exist in Pfr (active form) and Pr (inactive form) forms, which are interconvertible. When a PHY molecule absorbs Red light, it is converted from Pr to Pfr; when it absorbs Far−Red light, it is converted back to Pr [ 7 , 41 ]. This reversible conversion between Pr and Pfr serves as major molecular switches in the PHY signaling pathway, and their pathway and downstream components have been extensively studied.…”
Section: The Light Signaling Pathwaymentioning
confidence: 99%
“…The assimilative function of light provides the energy necessary for photosynthesis, suggesting light is the ultimate energy source for green plant metabolism, and the photosynthetic efficiency depends on the spectral wavelength (light quality) [ 2 , 3 , 4 ]. On the other hand, the signaling function of light activates and regulates many key signaling pathways related to plant photomorphogenesis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In developmental biology, the response of plant growth patterns to light spectra is known as photomorphogenesis, which occurs during seed germination, seedling development, and the transition from vegetative to anthesis (photoperiodic phenomenon) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assimilative function of light provides the energy necessary for photosynthesis, suggesting light is the ultimate energy source for green plant metabolism, and the photosynthetic efficiency depends on the spectral wavelength (light quality) [2][3][4]. On the other hand, the signaling function of light activates and regulates many key signaling pathways related to plant photomorphogenesis [5][6][7][8][9][10][11]. In developmental biology, the response of plant growth patterns to light spectra is known as photomorphogenesis, which occurs during seed germination, seedling development, and the transition from vegetative to anthesis (photoperiodic phenomenon) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%